2020
DOI: 10.1158/1535-7163.mct-19-0018
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of ZnO Nanoparticles against Human Small-Cell Lung Cancer in an Orthotopic Mouse Model

Abstract: Small-cell lung cancer, a highly malignant form of lung cancer, often responds to first-line treatments but relapses in most cases with resistance to further treatments. We tested zinc oxide (ZnO) nanoparticles against small-cell lung cancer and other cancer cell lines, in light of reported anticancer effects in vitro. Because of a strong safety record, ZnO nanoparticles are frequently used in biomedical research, including in cellular imaging and drug delivery, and have been used for many years in several com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 45 publications
0
59
0
Order By: Relevance
“…Furthermore, the crystallinity observed in the XRD spectrum was complemented by high-resolution TEM (HRTEM) studies. As shown in Figure 7 b, the observed diffraction lattice fringes in ZnONPs show d-spacing with an inter-planar distance of 0.260 nm between two fringes, which corresponds to d-spacing of the (002) crystal plane of ZnO [ 20 ]. Moreover, it has been reported that a decrease in the particle size increases the functionality of antimicrobial and anticancer agents due to the larger surface-to-volume ratio [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the crystallinity observed in the XRD spectrum was complemented by high-resolution TEM (HRTEM) studies. As shown in Figure 7 b, the observed diffraction lattice fringes in ZnONPs show d-spacing with an inter-planar distance of 0.260 nm between two fringes, which corresponds to d-spacing of the (002) crystal plane of ZnO [ 20 ]. Moreover, it has been reported that a decrease in the particle size increases the functionality of antimicrobial and anticancer agents due to the larger surface-to-volume ratio [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, zinc oxide nanoparticles (ZnONPs), a versatile drug delivery tool, have recently been reported to possess significant tumoricidal activity via ROS generation or the caspase-8 and p53 pathway [20][21][22]. However, a better understanding of the mechanistic model and the resultant cellular consequences is essential.…”
Section: Introductionmentioning
confidence: 99%
“…First, we exposed the cells with a range of concentrations (0-200 µg/mL) of ZnO NPs, SnO 2 -ZnO NPs, and SnO 2 -ZnO/rGO NCs for 24 h for cell viability assay. On the basis of cell viability results, we have chosen three moderate concentrations (10,25, and 50 µg/mL) of these samples for further experiments. For microscopic study we have chosen one concentration (50 µg/mL) of prepared samples.…”
Section: Characterizationmentioning
confidence: 99%
“…Due to unique physiochemical characteristics ZnO NPs have shown inherent selective toxicity against cancer cells while posing minimum effects to the normal cells. [9][10][11] ZnO NPs induce apoptosis in cancer cells through the generation of ROS and depletion of mitochondrial membrane potential (MMP) 12,13 Manipulation in intracellular ROS generation is a probable way to irreversibly damage cancerous cells selectively without applying much harm to normal cells. The ROS-generating potential of ZnO NPs is associated with its optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the anti-cancer effect of biosynthesized Zn NP was also found by Raajshree et al in the murine model of Dalton’s lymphoma ascites [ 16 ]. Tanino et al reported genotoxicity of ZnO NP and low viability of small-lung cancer in mice in response to treatment [ 17 ]. In most cases, effects on normal cells were minimal, and effective tumor inhibition was found.…”
Section: Introductionmentioning
confidence: 99%